Try factoring. You have a "+" for the last two terms, so we'll have + in the factors:
(?x + ?)(?x + ?) = 0
The first coefficient is 2, and the only factors of 2 are 1 and 2, so put these in for our first terms:
(2x + ?)(x + ?) = 0
Now we need to plug in factors of 5 so that the middle term ads up to 11. If we put the 5 on the right and the 1 on the left, we get (2x + 1)(x + 5) = 2x^2 + x + 10x + 5 = 2x^2 + 11x + 5, so that works.
Now that we have (2x + 1)(x + 5) = 0, we can solve for x. The product is zero, so one of these two terms must be zero. If 2x + 1 = 0, then x = -1/2. And if x+5 = 0, then x = -5. So those are the two solutions.
2007-05-15 16:14:25
·
answer #1
·
answered by Anonymous
·
5⤊
0⤋
Your friend is right 6x^2 - 2x = 0 x is a common factor, so take an x out x(6x - 2) = 0 Now, set both factors equal to 0 x = 0 6x - 2 = 0 Solve for x x = 0 6x - 2 = 0 6x = 2 x = 2/6 x = 1/3 The x-intercepts will be 0 and 1/3, like your friend said. EDIT: Yes, you're right, a is 6 and b is -2, just substitute x = -b/2a x = -(-2)/2(6) x = 4/12 x = 1/3, this is the x-coordinate of the vertex Now, substitute this into the equation to find the y-coordinate. 6x^2 - 2x = y 6(1/3)^2 - 2(1/3) = y 6(1/9) - (2/3) = y 2/3 - 2/3 = y 0 = y, the y-coordinate is 0 Therefore, the vertex is (1/3 , 0)
2016-05-19 16:01:09
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
Okay...so you have this problem and you kneed to fractor it out... the answer is (2x+1)(x+5). So to get this you had to you know that the first term in each of the parenthesis has to equal to the 2x^2. So that factors out to 2x and x. Now to get the next numbers you need the two numbers on the end to equal to the two end numbers multiplied. So 2 * 5 =10. What two number when you multiply them together do you get 10? 2 and 5. So you already have 2, so you no that the outside number in the second set of parenthesis is 5. Now the inner term has to be 1 and x because you need to get 11x. What I do is muliply the outer numbers and then add the middle numbers to get the middle number of the original. So 10 + 1 equals 11. So that is how you get (2x+1)(x+5). Now set each term equals to 0. You have 2x+1=0 and x+5=0. Solve for x in each equation and you get x= -1/2 and x= -5.
Hope that helps...Just play around with the numbers to get the factored form...
2007-05-15 16:23:38
·
answer #3
·
answered by livingall_4_god 2
·
1⤊
0⤋
2 x^2 + 11 x + 5 = 0
2 x^2 + 10 x + x + 5 = 0
2 x (x+5) + 1 (x+5)=0
(2x+1) * (x+5) = 0
2x +1 = 0 or X+5 = 0
x = -1/2 or x = -5
2007-05-15 16:14:24
·
answer #4
·
answered by phoenix 2
·
1⤊
0⤋
2x^2 + 11 + 5 = 0
2x^2 + x +10x + 5 = 0
2x(x+ 1/2) + 10(x+ 1/2) = 0
(2x + 10)(x+ 1/2) = 0
2(x + 5)(x+ 1/2) = 0
Thus x = -5 or x = -1/2
2007-05-15 16:14:15
·
answer #5
·
answered by skg 2
·
1⤊
0⤋
(2x+1)(x+5) = 0
2x+1 = 0 OR x+5 = 0
x= -1/2 OR x= -5
2007-05-15 16:13:41
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
This is factorable.
(2x+1)(x+5) = 0
2x+1 = 0 or x+5 = 0
x = -1/2 or x = -5
2007-05-15 16:12:27
·
answer #7
·
answered by MsMath 7
·
2⤊
1⤋
2x^2 + 11x + 5 = (2x+1)(x+5) so
2x^2 + 11x + 5 = 0 then
(2x+1)(x+5)=0 so
2x+1=0 .........x = -1/2 or
x+5= 0 ..........x = -5
2007-05-15 16:18:25
·
answer #8
·
answered by Trini 3
·
1⤊
0⤋
i did the problem and got the answer x= -5 and x= -1/2
2007-05-15 16:21:27
·
answer #9
·
answered by navi 2
·
0⤊
0⤋
Your answer is right because when you factor you get (2x+1)(x+5). When you solve them both for zero you get -1/2 and -5.
2007-05-15 16:15:44
·
answer #10
·
answered by ammaryusuf 3
·
1⤊
0⤋